Toista ajatellen Historiallisia ja kulttuurisia näkökulmia toiseuden kohtaamiseen - Kivistö, Sari (Tietolipas, 2022)
Human lives are crucially shaped by encounters of otherness - or, rather, various othernesses. This book explores the ethical challenge of developing an appropriate and respectful relation to other human beings by analyzing a number of historical and cultural cases of relating to the other. The topics range from barbarism, racist stereotypes, female rhetoric, and vampires to philosophical analyses of Finnish writers like Eino Leino and Väinö Linna, and from lyrical depictions of pain to an "antitheodicist" reflection on Primo Levi's Holocaust writing. A chapter on what it means to take a critical distance to other human beings in the context of the covid-19 pandemic concludes the volume. The authors approach these diverse issues (which are all aspects of the same basic problem of understanding and acknowledging otherness) from the perspective of an interdisciplinary humanistic reflection integrating literary analysis and philosophical argumentation.